Digital Literacy and Local Wisdom for Women-Led MSMEs: Pathways to Sustainable Rural Tourism in Lake Toba - Firinta Togatorop; Doris Yolanda Saragih; Hengki Mangiring Parulian Simarmata (Fakultas Ekonomi Universitas Simalungun, 2025)
Research on digital literacy in MSMEs has gained attention; however, its intersection with women’s entrepreneurship and cultural heritage in sustainable tourism remains underexplored. This study seeks to fill this gap by examining how digital literacy and local wisdom jointly influence the sustainability of women-led MSMEs in Lake Toba, Indonesia, a UNESCO Global Geopark. A qualitative approach was applied through in-depth interviews with 50 women entrepreneurs engaged in culinary, handicraft, homestay, and creative sectors, along with officials from the Cooperative and the MSME Office of Samosir Regency. The data were analyzed using thematic coding to uncover patterns of opportunities, constraints, and resilience strategies. The study reveals that women entrepreneurs serve as both economic actors and cultural custodians yet face significant challenges, including low digital literacy, limited financing access, seasonal dependency, and domestic burdens. Despite these barriers, the findings highlight a novel synergy between digital literacy and local wisdom that fosters value creation, eco-friendly innovation, and cultural-based brand storytelling as pathways to sustainability. As this was a single-case qualitative study, the results were context-specific and may not be broadly generalizable. Theoretically, this study integrates digital literacy and cultural heritage into the MSME sustainability discourse. Practically, it provides policy recommendations and training models to promote women’s empowerment and sustainable rural tourism.